A systematic literature review on blockchain governance - Liu, Yue; Lu, Qinghua; Zhu, Liming; Paik, Hye-Young; Staples, Mark (The Journal of systems and software, 2023)
Blockchain has been increasingly used as a component to enable decentralisation in software architecture for a variety of applications. Blockchain governance has received considerable attention to ensure the safe and appropriate use and evolution of blockchain, especially after the Ethereum DAO attack in 2016. However, there are no systematic efforts to analyse existing governance solutions. To understand the state-of-the-art of blockchain governance, we conducted a systematic literature review with 37 primary studies. The extracted data from primary studies are synthesised to answer identified research questions. The study results reveal several major findings: (1) governance can improve the adaptability and upgradability of blockchain, whilst the current studies neglect broader ethical responsibilities as the objectives of blockchain governance; (2) governance is along with the development process of a blockchain platform, while ecosystem-level governance process is missing, and; (3) the responsibilities and capabilities of blockchain stakeholders are briefly discussed, whilst the decision rights, accountability, and incentives of blockchain stakeholders are still under studied. We provide actionable guidelines for academia and practitioners to use throughout the lifecycle of blockchain, and discuss future trends to support researchers in this area. •We identify a set of 37 primary studies related to blockchain governance.•We present data synthesis to reflect state-of-the-art in blockchain governance.•We provide insights and research agenda based on the SLR results.